Leadership: a view from organizational theories - Palafox Soto, María Olivia (2020)
Leadership is an essential part of the organizational management, which has been studied from different perspectives. Therefore, this article shows the theoretical approach of these aspects from the perspective of organizational theories, with a historical, analytical and critical analysis of the contributions, taking as reference the methodology proposed by Fink, through a literature review. The above, allows to affirm that the existence of leadership in the organizations, is dependent on the coexistence of motivation, communication, power, authority, among other elements, that give it life, presence and essence in all types of organizations thus contributing to the permanence of the same.